Challenges of College Students’ Ideological and Political and Psychological Education in the Information Age - He, Xiaoqing; Dong, Xiangrong; Liu, Li; Zou, Yulin (Frontiers in Psychology, 2021)
The purpose of the study is to analyze the current situation of ideological and political education and psychological education of college students, and explore the challenges faced by these two kinds of education in the information age. First, different research methods, such as literature research, questionnaire survey, and interdisciplinary research are used to investigate and study the current situation of ideological and political education and psychological education of college students. Second, the survey data are analyzed to reveal the challenges they have to encounter. The results show that there are many problems in ideological and political education, which need to be improved and strengthened. The Internet has a strong attraction for college students, but many college students’ purpose of getting online is not clear. Although it plays an important role in improving the teaching quality of helping college students establish correct attitudes towards their study, values, life, and society, ideological and political education lacks strong pertinence and effectiveness due to the professionalism of the teachers. And the negative impact of network information on college students’ ideological and political education is also obvious. 11.4% of the respondents believe that network information affects their physical and mental health. 8.4% of the respondents believe that harmful information on the network is easy to induce students to behave wrongly. 41% believe that computer games distract them from learning, which indicates that the negative impact of network information on college students cannot be underestimated and it is imperative to strengthen college students’ ideological and political education. The research provides a useful reference for the ideological and political psychological education in the information environment and helps to solve the problem in the ideological and political education and psychological education of college students.